Envisioning a sustainable consumption future. Issue 4 (30th July 2019) - Aitken, Rob; Watkins, Leah; Kemp, Sophie
Abstract : Purpose: The purpose of this study is to understand what a sustainable future would look like and the nature of the changes needed to achieve it. Continued reliance on economic growth to meet the demands of a growing population is unsustainable and comes at an unacceptable social and environmental cost. Given these increasing demands, radical changes to present practices of production and consumption are needed to enable a sustainable future. Design/methodology/approach: To address this the projective technique of backcasting was used in a pilot study to explore student visions of a sustainable future. An integrative framework comprising housing, clothing, travel, leisure and food provided the structure for six focus group discussions. Findings: Thematic analysis identified three key characteristics of a sustainable consumption future, namely, efficiency, sharing and community and three critical elements, namely, the role of government, education and technology, necessary for its achievement. Research limitations/implications: Demonstrating the usefulness of backcasting will encourage its application in a wider range of consumption contexts with a broader range of participants. The vision of a sustainable future provides a blueprint that identifies its nature, and the basis upon which decisions to achieve it can be made. Originality/value: The research introduces the technique of backcasting and demonstrates its usefulness when dealing with complex problems, where there is a need for radical change and when the status quo is not sustainable. Unexpectedly, results suggest a commitment to prosocial values, collaborative experience, collective action and the importance of community. Research and social implications demonstrating the usefulness of backcasting will encourage its application in a wider range of consumption contexts with a broader range of participants. The vision of a sustainable future provides a blueprint that identifies its nature, and the basis upon which decisions to achieve it can be made.